Reliability of Metformin’s protective effects against doxorubicin-induced cardiotoxicity: a meta-analysis of animal studies - Sun, Ming-Li; Chen, Wei; Wang, Xing-He (Frontiers in Pharmacology, 2024)
Background: The protective effects of metformin (Met) against doxorubicin (Dox)induced cardiotoxicity via potential hypotheses of mechanisms of action with unknown reliability and credibility. Objectives: This study aimed to investigate the protective effects of Met against Doxinduced cardiotoxicity and the underlying mechanisms of action, as well as examine their reliability and credibility. Methods: A comprehensive search was conducted within the PubMed, Embase, Web of Science, Science Direct, Scopus, and CNKI databases from inception to December 31, 2023. Animal experiments evaluating the efficacy of Met against Dox-induced cardiotoxicity were included in this study. The primary efficacy outcomes were markers of myocardial injury. Effect size was measured using the standardized mean difference for continuous variables. Data were pooled using a random-effects model in the Stata 18 statistical software package. Results: Twenty-one studies involving 203-208 animals treated with Dox and 271-276 animals treated with Dox and Met were included in this analysis. Quality assessment revealed high-quality scores. Pooled results favored Met treatment based on the serum lactate dehydrogenase (LDH), creatine kinase-myocardial band (CK-MB), cardiac troponin I (cTnI), and aspartate aminotransferase levels. Sensitivity analysis using the leave-one-out method demonstrated stable results. Funnel plots, Egger's test, and Begg's test confirmed potential publication bias. The oxidative stress hypothesis has been investigated extensively based on abundant evidence. Conclusions: Met is effective and safe for protecting against Dox-induced cardiotoxicity, thus making it an appropriate drug for clinical investigation. The oxidative stress hypothesis of mechanism of action is well established with highest reliability and credibility.